Pathological findings in rainbow trout (oncorhynchus mykiss, walbaum 1792) in experimental vagococcus salmoninarum infection - S. Serap Birincioğlu; Hamdi Avcı; T. Tansel Tanrikulu; E.Tuğrul Epikmen; M. Lütfi Avsever (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to induce Vagococcus salmoninarum (V. salmoninarum) experimental infection in adult fish through different routes [intraperitoneal (IP) and immersion (IM)] to investigate clinical, macroscopical and histopathological findings. Materials and Methods: Totally 4 groups (experiment immersion-EIM, experiment peritoneal-EIP and 2 controls) were used. As material, overall 60 rainbow trout were used. Fishes were infected with Vagococcus salmoninarum (accession number: Kj685901) strain. For histopathological examinations, all tissue samples were fixed and than fixation samples routinely were processed. Tissue sections stained with haematoxylin-eosin and examined using light microscope. DNA extractions of the isolate were made for the molecular analysis of the bacteria and then, specific primers were used to identify V. salmoninarum. The PCR product from isolate V. salmoninarum was used for sequencing. Results: In both groups, mortality rate was 100%. In macroscopic examination, abdominal swelling, depigmentation of the skin, hemorrhages at the base of the fins, swelling in kidneys and a thick and yellow-orange fluid in the intestine were seen. These findings were observed in both groups, but were more severe in EIP group than in EIM group. In histopathologic examination, the course of the disease ranged from acute form to chronic form in both groups. In acute form, haemorrhage and telangiectasia in the gills and increase in melanomacrophage centers were detected. In chronic form, degeneration and necrosis in the kidney and epicarditis in three cases (EIP) were observed. Elevated numbers and degranulation of eosinophilic granular cells (EGC) in the submucosa of the digestive system were also observed. Degeneration was seen in gastric epithelium and shedding of intestinal mucosa epithelium. Conclusion: In this study, approachs of V. salmoninarum infection in adult rainbow trout, the differences between the findings in experimental infection and natural infection is recommended to be taken into account.